Ischemic tolerance - blessing or curse - Burda, J; Burda, R (Physiological research, 2021)
Application of knowledge about ischemic tolerance to clinic requires the solid understanding of mechanism of creation of this phenomenon. This review summarizes research that has been carried out in many laboratories over a long period of time, but the main focus will be on own experimental research. The main emphasis is devoted to the possibility of preparing full tolerance in the donor's body and its transfer to the patient in the form of activated blood plasma. Such plasma could be administered as soon as the patient is transported to the hospital and would take effect immediately after administration to the patient's bloodstream. One chapter is also devoted to anticonditioning, i.e. the possibility of preventing the activation of tolerance. Anticonditioning could be used to treat oncologic patients. We expect that this method could increase effectiveness of cancer treatment. Cross-tolerance with a wide range of diverse stressors gives us the courage to assume that activated plasma can significantly help with a wide range of pathological events.
Keywords: Ischemic Preconditioning; fyziologický stres; Animals; přivykání k ischémii; Stress, Physiological; ischemický postconditioning; lidé; zvířata; Ischemic Postconditioning; Humans